TEACHING LISTENING TO YOUNG LEARNER - Egamberdiyeva Irodaxon Abduraximovna; Nabiyeva Begoyim Adxamjon qizi (TADQIQOTLAR.UZ, 2023)
Annotation: Listening is both a goal and a means of learning. Learning the semantic perception of speech by ear involves the learners performing exercises for the formation of general auditory skills, speech exercises and subsequent educational work with audio text, that is, listening training is aimed at developing and improving the mechanisms of listening.